Contextual Thinking Ability in Learning Somatic, Auditory, Visual and Intellectual Models with Recitation Strategies at SMP Negeri 1 Jetis Ponorogo - Faninda Novika Pertiwi*; Fauji Agusta (JIPI (Jurnal IPA dan Pembelajaran IPA), 2023)
Students' ability to think contextually is still not optimal. The ability to think contextually is essential for students to have in helping to understand good learning by linking the surrounding environment. Based on a preliminary study conducted at SMP Negeri 1 Jetis Ponorogo, students' ability to think contextually is still relatively low, namely an average of 68. Therefore, it is necessary to apply innovative learning models such as the SAVI learning model (somatic, auditory, visual, and intellectual) with recitation strategies. The SAVI learning model (somatic, auditory, visual and intellectual) can make students more active because the learning process integrates all senses. This study uses a quantitative approach to the type of experimental research. The research design used is a true experimental design with a posttest only control design. The population in this study was class VIII at SMPN 1 Jetis Ponorogo with a total of 8 classes. The sample in this study was selected using purposive sampling, namely class VIII E and class VIII G. This study used a descriptive test as an instrument for data collection. The results of this study are that the SAVI learning model is effective on students' contextual thinking skills at SMP Negeri 1 Jetis Ponorogo which is characterized by the one-tailed t-test results which produce a p-value of 0.000 less than alpha (0.05) which indicates that the experimental class's ability to think contextually with an average higher than the control class. The average value of the experimental class was 88.3, while the control class obtained an average value of 69.0